Distribution of Teak under Different Silvo-climatic Conditions in some Parts of Western Ghats - Singh, Jasbir; Prasad, K. G.; Gupta, G. N. (Indian Forester, 1986)
Present work was an attempt to study the influence of climatic, physiographic and edaphic factors on the growth and distrihution of Teak (Tectono grandis) in the eastern slope of western ghats. Based on soil analytical and teak density data obtained during the survey of Mudumalai Wildlife sanctuary and Coimbatore Forest Division in Tamil Nadu it was observed that, in general, teak prefers moderately deep, well drained. Medium textured soil, moderate temperature and gentle slopes. The data also suggest that high to very high teak density sites have relatively higher organic carbon; exchangeable calcium and cation exchangeable capacity.